Application of 3D Printing Technology and Porous Nano-Ceramic Decorative Sheet in Interior Landscape Design - Baojin Qiu; Xun Xu (International Journal of Analytical Chemistry)
In order to solve the problems that the traditional ceramic method is difficult to form porous ceramics with complex structures, the mold production cycle is long, and the cost is high, the authors propose the application of 3D printing technology and porous nano-ceramic decorative sheet in interior landscape design. Based on the use of photocuring molding technology to make high-precision regular resin molds, optimize the low-viscosity, high-solid content alumina ceramic slurry required by the gel injection molding process and form alumina ceramic blanks by means of a vacuum pressure process, so as to realize the net shape of complex structural porous ceramic parts. In view of the filling problem of ceramic slurry in complex structure in the process, the effects of slurry pH value, dispersant dosage, and vacuum pressurization process on ceramic molding were studied, and parameters such as porosity and compressive strength of the green body were tested. Experimental results show the following. Under the conditions of pH value of 9, mass fraction of dispersant of 0.4%, and vacuum pressure of 90 min, alumina ceramics with a volume fraction of 52% can be prepared, the porosity is 51.5%, and the compressive strength is 40.1 MPa. The ceramic material prepared by this process has complete structure and smooth surface and can be used as a process for preparing porous ceramic parts with complex structure.